2015
DOI: 10.1093/mnras/stv2308
|View full text |Cite
|
Sign up to set email alerts
|

Gaiatransient detection efficiency: hunting for nuclear transients

Abstract: We present a study of the detectability of transient events associated with galaxies for the Gaia European Space Agency astrometric mission. We simulated the on-board detections, and on-ground processing for a mock galaxy catalogue to establish the properties required for the discovery of transient events by Gaia, specifically tidal disruption events (TDEs) and supernovae (SNe). Transients may either be discovered by the on-board detection of a new source or by the brightening of a previously known source. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 54 publications
0
19
1
Order By: Relevance
“…For eROSITA we predict between 669 and 849 detections annually, which is again comparable to the results of Mageshwaran & Mangalam (2015), who find an expected detection rate of 679.5 ± 195 yr −1 , and is also comparable to the results of Khabibullin et al (2014), who predict several thousand detections over the full length of eRASS. For Gaia, our expected detection rates of 81-182 yr −1 are significantly higher than that predicted by Blagorodnova et al (2016), who expect only 20-30 TDEs per year. This discrepancy becomes even more concerning when one considers that Gaia has not yet alerted the detection of a single TDE.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…For eROSITA we predict between 669 and 849 detections annually, which is again comparable to the results of Mageshwaran & Mangalam (2015), who find an expected detection rate of 679.5 ± 195 yr −1 , and is also comparable to the results of Khabibullin et al (2014), who predict several thousand detections over the full length of eRASS. For Gaia, our expected detection rates of 81-182 yr −1 are significantly higher than that predicted by Blagorodnova et al (2016), who expect only 20-30 TDEs per year. This discrepancy becomes even more concerning when one considers that Gaia has not yet alerted the detection of a single TDE.…”
Section: Discussioncontrasting
confidence: 70%
“…The satellite Gaia (Perryman et al 2001;Gaia Collaboration et al 2016) began observing in 2014, and has since been undertaking a 5 year mission primarily aimed at mapping the positions and motions of stars in our galaxy. To achieve this, however, multiple observations of each target are required, making Gaia naturally suited to detecting transient events, including TDEs (Gaia's transient detection capabilities are discussed thoroughly in Blagorodnova et al 2016). When considering Gaia, we use the same methodology as with LSST.…”
Section: Gaiamentioning
confidence: 99%
“…transients -likely SNe close to the host centre or AGN variability -observed within 0.5 arcsec from their host centre if the host is recognised using external catalogues) which is roughly less than 25 per cent of the expected number of supernovae and TDEs. We note that the predictions of Blagorodnova et al (2016) do not include events due to AGN variability, which are a significant contributor to the published Gaia Alerts, hence the missing fraction of nuclear transients is probably significantly larger than 75 per cent.…”
Section: Introductionmentioning
confidence: 88%
“…In this study we performed a large-scale and systematic search for transient events in the nuclei of galaxies detectable by Gaia between mid-2016 and mid-2017. We started with objects classified as "galaxy" by the Sloan Digital Sky Survey 1 http://tde.space 2 The value of uncertainty from Blagorodnova et al (2016) was corrected (private communication). Poisson noise was not taken into account in the simulations by Blagorodnova et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…As of October 2016, the Catalina Real-Time Transient Survey (CRTS, Drake et al 2009) had detected almost 1400 new CVs, the All-Sky Automated Survey for SuperNovae (ASAS-SN, Shappee et al 2014) had found over 750 and the Mobile Astronomical System of TElescope-Robots (MASTER, Lipunov et al 2010) had discovered almost 750. The Gaia astrometric surveying satellite is also now discovering transient events, including CVs, at a rate of several per day (Wyrzykowski et al 2012;Blagorodnova et al 2016). On top of these, many hundreds have been identified in the Sloan Digital Sky Survey (SDSS, Gänsicke et al 2009;Szkody et al 2011) and by a vast network of amateur astronomers.…”
Section: A N D I Dat E S E L E C T I O Nmentioning
confidence: 99%